2023
DOI: 10.1002/ohn.317
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Configuring Deep Learning Network for Segmentation of Temporal Bone Anatomy in Cone‐Beam CT Imaging

Abstract: ObjectivePreoperative planning for otologic or neurotologic procedures often requires manual segmentation of relevant structures, which can be tedious and time‐consuming. Automated methods for segmenting multiple geometrically complex structures can not only streamline preoperative planning but also augment minimally invasive and/or robot‐assisted procedures in this space. This study evaluates a state‐of‐the‐art deep learning pipeline for semantic segmentation of temporal bone anatomy.Study DesignA descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Most recently, Ding et al describe the use of the nnU-Net architecture to perform automated segmentation on 15 CBCTs. 12 nnU-Net, based on a U-net backbone, can automatically self-configure to new data sets. It achieves this by automatically tuning hyperparameters to configure to new data sets.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most recently, Ding et al describe the use of the nnU-Net architecture to perform automated segmentation on 15 CBCTs. 12 nnU-Net, based on a U-net backbone, can automatically self-configure to new data sets. It achieves this by automatically tuning hyperparameters to configure to new data sets.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the DSC for the malleus of 0.914 ± 0.03 and 0.916 ± 0.034 for the incus, the DSC for the stapes was only 0.560 ± 0.106. 12 Modified Haudorff distance (mHD) was 0.044 ± 0.024 mm for the malleus, 0.051 ± 0.027 mm for the incus and 0.147 ± 0.113 for the stapes. Constrained linear regression between DSC and mHD showed that DSC for small structures like the stapes decreased significantly compared to mHD (p < 0.0001) versus larger or thicker structures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Highly accurate automatic segmentation of radiological images has been demonstrated in CT scans [107], MRI scans [108] and cone-beam scans [109,110]. After selecting the region of interest, deep learning models can be specifically trained to classify specific diseases, such as chronic otitis media [111], cholesteatoma [112,113], otosclerosis [114,115], mastoiditis [116,117], and Meniere disease [118,119], achieving detection results comparable to subspeciality-trained radiologists.…”
Section: Imaging In Otologymentioning
confidence: 99%